Battery cathode materials and their preparation methods
By leveraging the synergistic effect of polyaluminum iron silicate, chitosan, and medical aluminum phosphate gel, combined with vanadium oxide precipitation and calcination processes, the problem of impurity removal from vanadium pentoxide was solved, resulting in the preparation of high-purity battery-grade V2O5 and optimization of the performance of battery cathode materials.
Patent Information
- Application Number
- CN202511206524.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-27
- Publication Date
- 2025-12-02
- Estimated Expiration
- 2045-08-27
AI Technical Summary
Existing technologies are insufficient to efficiently remove impurities such as Fe, Al, Si, and P from vanadium pentoxide, resulting in lengthy traditional processes, low vanadium recovery rates, and organic pollution, making it difficult to prepare high-purity battery-grade V2O5.
The synergistic effect of polyaluminum iron silicate and chitosan combined with medical aluminum phosphate gel was used to pretreat and purify vanadium-containing leachate. High-purity vanadium pentoxide was then prepared by vanadium oxidation precipitation and calcination, and finally, battery cathode material was prepared.
It significantly improves the efficiency of impurity removal, realizes the preparation of high-purity vanadium pentoxide, meets battery-grade standards, simplifies the process, reduces costs and environmental pollution.
Smart Images

Figure CN120717509B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of batteries, specifically relating to a battery cathode material and its preparation method. Background Technology
[0002] The cathode material of a battery is one of the core factors that determine battery performance. Its physicochemical properties directly affect key indicators such as energy density, power density, cycle life, safety, and cost.
[0003] Vanadium pentoxide (V₂O₅) is a key raw material for battery cathode materials (such as LiV₃O₈ for lithium-ion batteries), and its purity directly affects battery performance and cycle life. Currently, V₂O₅ is mainly prepared industrially through acid / alkali leaching of vanadium-containing ores or spent catalysts. However, impurities such as Fe, Al, Si, and P in the leaching solution are difficult to remove deeply, resulting in problems such as lengthy processes, low vanadium recovery rates, and organic pollution in traditional processes, making it difficult to meet the stringent requirements of battery-grade V₂O₅ (purity ≥ 99.95%).
[0004] In existing technologies, chemical precipitation methods (such as ammonium salt precipitation of vanadium) easily cause Fe and Al co-precipitation, requiring multiple pH adjustments and reduction processes, resulting in complex processes and high vanadium loss rates; solvent extraction methods (such as the P2O4 system) can efficiently separate vanadium, but organic solvents are prone to emulsification and introduce residues; biosorption methods (such as microbial impurity removal) have slow reaction rates and limited effectiveness in removing phosphorus. Furthermore, phosphorus impurities (PO4)... 3- The removal of vanadium is particularly difficult, and the traditional iron salt precipitation method is prone to vanadium adsorption loss, which restricts the industrial production of high-purity V2O5.
[0005] Therefore, there is still room for improvement in the process of preparing high-purity vanadium pentoxide and using it as a raw material to prepare battery cathode materials. Summary of the Invention
[0006] The main objective of this invention is to address the shortcomings of the existing technology by providing a short-process, low-cost, green, and efficient V2O5 purification process and a method for preparing battery cathode materials using the purified V2O5 as raw material.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] According to a first aspect of the present invention, a method for preparing a battery cathode material is provided, comprising the following steps:
[0009] S1: Pretreatment of vanadium-containing leaching solution with polyaluminum iron silicate to obtain pretreated solution;
[0010] S2: The pretreatment solution is purified using chitosan and medical aluminum phosphate gel to obtain a purified solution;
[0011] S3: Add an oxidant and an ammonium source to the purified liquid to oxidize and precipitate vanadium, and obtain ammonium metavanadate precipitate;
[0012] S4: Calcining the ammonium metavanadate precipitate to obtain high-purity vanadium pentoxide;
[0013] S5: Use the high-purity vanadium pentoxide to prepare battery cathode material.
[0014] According to some embodiments of the present invention, step S1 includes: adjusting the pH of the vanadium-containing leachate to 1.5-2.5, heating the vanadium-containing leachate to 60-90°C, then adding the polyaluminum ferric silicate, stirring for a first time, and then separating the solid and liquid to obtain the pretreated solution.
[0015] According to some embodiments of the present invention, in step S1, the amount of polyaluminum ferric silicate added is 1-1.2 times the theoretical amount added.
[0016] According to some embodiments of the present invention, in step S1, the first time is 30-120 minutes.
[0017] According to some embodiments of the present invention, in step S1, the pH of the vanadium-containing leachate is adjusted using a sulfuric acid solution.
[0018] According to some embodiments of the present invention, step S2 includes: adjusting the pH of the pretreatment solution to 3-4, adding chitosan and medical aluminum phosphate gel, reacting at 60-90°C for a second time, and obtaining the purified solution through solid-liquid separation.
[0019] According to some embodiments of the present invention, in step S2, the amount of chitosan and the medical aluminum phosphate gel added is 1-1.15 times the theoretical amount added.
[0020] According to some embodiments of the present invention, in step S2, the pH of the pretreatment solution is adjusted using one or more of NaOH, urea, or ammonia.
[0021] According to some embodiments of the present invention, in step S2, the second time is 40-90 minutes.
[0022] According to some embodiments of the present invention, step S3 includes: adding the oxidant to the purified liquid for a third time, adjusting the pH to 6.5-8.5 with the ammonium source at room temperature-100°C, precipitating for a fourth time, and obtaining the ammonium metavanadate precipitate by solid-liquid separation.
[0023] According to some embodiments of the present invention, in step S3, the oxidant is NaClO3 or H2O2.
[0024] According to some embodiments of the present invention, in step S3, the volume of the oxidant added is 3-7% of the volume of the purified liquid.
[0025] According to some embodiments of the present invention, in step S3, the third time is 20-40 minutes.
[0026] According to some embodiments of the present invention, in step S3, the ammonium source is ammonia, ammonium carbonate, or ammonium bicarbonate.
[0027] According to some embodiments of the present invention, in step S3, the fourth time is 1.5-2.5 hours.
[0028] According to some embodiments of the present invention, step S4 includes: heating the ammonium metavanadate precipitate at 3-10℃ / min in an oxygen atmosphere, holding it at 300℃ for 30 minutes, and calcining it at 440-600℃ for 1-4 hours to obtain high-purity vanadium pentoxide.
[0029] According to a second aspect of the present invention, a battery cathode material is provided, which is prepared by the above-described preparation method.
[0030] By adopting the above technical solution, the present invention has the following beneficial effects:
[0031] This invention innovatively combines the synergistic effect of biological agents (chitosan) and inorganic flocculants (polyaluminum ferric silicate), significantly improving the removal efficiency of impurities such as Fe and Al. Furthermore, it introduces medical-grade aluminum phosphate gel for targeted phosphorus removal, solving the problem of vanadium loss caused by traditional iron salt phosphorus removal. This achieves highly efficient purification and short-process treatment of vanadium-containing leachate, avoiding the use of organic solvents, making it environmentally friendly. It produces high-purity vanadium pentoxide with stable purity meeting battery-grade standards and the requirements for use as a battery cathode material. This high-purity vanadium pentoxide can be used to prepare high-performance battery cathode materials. Attached Figure Description
[0032] Figure 1 A flowchart illustrating the preparation method of the battery cathode material provided by this invention. Detailed Implementation
[0033] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0034] Specific embodiments of the invention are disclosed herein as needed; however, it should be understood that the embodiments disclosed herein are merely examples of the invention that may be implemented in various alternative forms. In the following description, various operating parameters and components are described in several contemplated embodiments. These specific parameters and components are provided as examples only and are not intended to be limiting.
[0035] The first aspect of the present invention provides a method for preparing a battery cathode material, such as... Figure 1 As shown, the method includes the following steps: S1: Pretreatment of vanadium-containing leachate with polyaluminum iron silicate to obtain pretreated solution; S2: Purification of pretreated solution with chitosan and medical aluminum phosphate gel to obtain purified solution; S3: Adding oxidant and ammonium source to purified solution to oxidize and precipitate vanadium to obtain ammonium metavanadate precipitate; S4: Calcination of ammonium metavanadate precipitate to obtain high-purity vanadium pentoxide; S5: Preparation of battery cathode material using high-purity vanadium pentoxide.
[0036] This invention innovatively combines the synergistic effect of biological agents (chitosan) and inorganic flocculants (polyaluminum ferric silicate), significantly improving the removal efficiency of impurities such as Fe and Al. Furthermore, it introduces medical-grade aluminum phosphate gel for targeted phosphorus removal, solving the vanadium loss problem caused by traditional iron salt phosphorus removal. This achieves highly efficient purification and short-process treatment of vanadium-containing leachate, avoiding the use of organic solvents, making it environmentally friendly. It produces high-purity vanadium pentoxide with stable purity meeting battery-grade standards and the requirements for use as a battery cathode material. This high-purity vanadium pentoxide can be used to prepare high-performance battery cathode materials.
[0037] In this invention, vanadium-containing leachate refers to a solution containing vanadium. This invention does not specify the composition of the vanadium-containing leachate. The method of this invention is particularly suitable for treating vanadium-containing leachates containing impurities such as iron, aluminum, silicon, and phosphorus.
[0038] The present invention will now be described in detail with reference to each step.
[0039] In step S1, the vanadium-containing leachate is pretreated using polyaluminum ferric silicate to precipitate colloidal silicon and some heavy metals, such as small amounts of iron, manganese, chromium, copper, zinc, lead, cobalt and other impurities brought in from mineral processing and smelting.
[0040] Polyaluminum iron silicate (PSAF) is a highly efficient inorganic polymeric flocculant. Based on the positively charged groups, long-chain structure, and active functional groups in its molecular structure, it achieves the removal of colloidal silica and some heavy metals through a combination of functions such as charge neutralization, adsorption, and co-precipitation.
[0041] The impurity removal mechanism of polyaluminum iron silicate (PSAF) is explained as follows: Adsorption and co-precipitation: PSAF encapsulates heavy metal ions through the adsorption of its polymer chains and the formation of flocculants, co-precipitating them with colloidal silica (SiO2·nH2O). Charge neutralization: Heavy metal ions are usually positively charged, while the hydrolysis products of PSAF are positively charged (such as Al). 3+ Fe 3+ Hydroxyl complexes or negatively charged compounds (such as polysilicic acid) can adsorb anionic heavy metals (such as arsenates) or form precipitates with cationic heavy metals through charge interactions.
[0042] In some embodiments, step S1 includes: adjusting the pH of the vanadium-containing leachate to 1.5-2.5, heating the vanadium-containing leachate to 60-90°C, then adding polyaluminum ferric silicate, stirring for a first time, and obtaining a pretreated solution through solid-liquid separation.
[0043] Adjusting the pH of the vanadium-containing leachate to 1.5-2.5 helps ensure the purification effect of polyaluminum ferric silicate. The pH can typically, but not limitedly, be set to 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, or 2.5.
[0044] In some embodiments, the pH of the vanadium-containing leachate is adjusted using a sulfuric acid solution.
[0045] Heating the vanadium-containing leachate to 60-90°C helps maintain a suitable reaction rate; too low a temperature will slow down the reaction. Typical, but not limited, heating temperatures can be set to 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, or 90°C.
[0046] In some embodiments, the amount of polyaluminum ferric silicate added is 1-1.2 times the theoretical amount to ensure sufficient removal of impurities. The amount of polyaluminum ferric silicate added is typically, but not limited to, 1.1 times, or 1.2 times the theoretical amount. Here, "theoretical amount" refers to the amount required to remove silicon and some heavy metals; specifically, the amount of polyaluminum ferric silicate added is 1-1.2 times the total molar amount of silicon and some heavy metals to be removed.
[0047] In some embodiments, the first time is 30-120 minutes. The first time can typically, but not in a limited way, be set to 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, 110 minutes, or 120 minutes.
[0048] In step S2, chitosan and medical aluminum phosphate gel are used to purify the pretreatment solution, aiming to remove impurities such as iron, aluminum, and phosphorus.
[0049] The impurity removal mechanism of chitosan is explained as follows: Adsorption and complexation: The amino group (-NH2) of chitosan is protonated to -NH3 under acidic or neutral conditions. + It can adsorb anionic impurities (such as phosphate ions PO4) through electrostatic adsorption. 3- (Iron / aluminum oxygen-containing anions). The hydroxyl and amino groups of chitosan can also react with Fe. 3+ Al 3+ When metal ions form stable chelates, especially for high-valence metal ions (such as Fe), 3+ Chitosan has a strong adsorption capacity. Flocculation: The long-chain structure of chitosan can adsorb colloidal particles (such as Fe(OH)3 and Al(OH)3 colloids) through a bridging effect, forming large flocs that settle. Selectivity: It has a high affinity for Fe... 3+ Al 3+ The adsorption capacity is much stronger than that of Ca. 2+ Mg 2+ Divalent ions.
[0050] The impurity removal mechanism of medical aluminum phosphate gel is explained as follows: Ion exchange and surface adsorption: The surface of aluminum phosphate gel is rich in Al. 3+ and PO4 3- Sites that can adsorb Fe in solution through ion exchange 3+ Al 3+ (with Al) 3+ (Competitive combination) or PO4 3- (Competing with phosphate ions in the gel). Medical aluminum phosphate gel is particularly effective at removing phosphorus (P) because aluminum phosphate itself is a poorly soluble compound (with extremely low Ksp), which can promote the removal of free PO4 in the solution. 3- AlPO4 coprecipitates. Coprecipitation occurs when Fe is present in the solution. 3+ This may generate FePO4 precipitate (similar in structure to AlPO4), simultaneously removing iron and phosphorus.
[0051] The synergistic purification effect of chitosan and medical aluminum phosphate gel is explained as follows: Stepwise action: Chitosan preferentially adsorbs free Fe... 3+ Al 3+ And colloidal particles, reducing metal impurities. Aluminum phosphate gel further removes phosphorus deeply through ion exchange and coprecipitation, and captures residual iron and aluminum. Complementarity: Chitosan is more effective for organic colloids and metal ions, while aluminum phosphate gel is more effective for inorganic phosphate and Al. 3+ / Fe 3+ The removal is more thorough.
[0052] In some embodiments, step S2 includes: adjusting the pH of the pretreatment solution to 3-4, adding chitosan and medical aluminum phosphate gel, reacting at 60-90°C for a second time, and obtaining a purified solution through solid-liquid separation.
[0053] Adjusting the pH of the pretreatment solution to 3-4, avoiding a strongly acidic environment, helps to achieve better results. The pH can typically, but not limited to, be set to 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, or 4.0.
[0054] Setting the reaction temperature to 60-90℃ helps maintain a suitable reaction rate; too low a temperature will slow down the reaction. Typical, but not limited, reaction temperatures can be set to 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, or 90℃.
[0055] In some embodiments, an alkaline agent is used to adjust the pH of the pretreatment solution to 3-4. Specifically, one or more of NaOH, urea, or ammonia solution can be used to adjust the pH of the pretreatment solution.
[0056] Preferably, in some embodiments, chitosan is added first to adsorb metal ions, and then medical aluminum phosphate gel is added to remove phosphorus, thus avoiding competitive adsorption.
[0057] In some embodiments, chitosan and medical aluminum phosphate gel can be pre-prepared into solutions of a certain concentration and then added to the pretreatment solution in solution form. For example, chitosan (degree of deacetylation ≥90%) can be prepared into a solution with a concentration of 0.5 g / L, and medical aluminum phosphate gel can be prepared into a solution with a concentration of 0.1 g / L.
[0058] In some embodiments, the amounts of chitosan and medical aluminum phosphate gel added are adjusted according to the amount of impurity elements in the vanadium solution, and the added amount is 1-1.15 times the theoretical added amount. Here, "theoretical added amount" refers to the amount required to remove the corresponding impurity element. Specifically, the amount of chitosan added is 1-1.15 times the total molar amount of Fe and Al impurities, and the amount of medical aluminum phosphate gel added is 1-1.15 times the molar amount of P.
[0059] In some embodiments, the second time is 40-90 minutes. The second time can typically, but not in a limiting way, be set to 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, or 90 minutes.
[0060] In a specific example, step S2 includes: adjusting the pH to 3-4 with an alkaline material (NaOH, urea, or ammonia, one or both), adding 0.5 g / L chitosan (deacetylation degree ≥90%) and 0.1 g / L medical aluminum phosphate gel. The amount added is adjusted according to the amount of impurity elements in the vanadium solution, and the amount added is 1-1.15 times the theoretical amount. The reaction is carried out for 40-90 minutes, and the purified solution is obtained by filtration. At this time, the contents of Fe, Al, and P are all <5 ppm.
[0061] In step S3, an oxidant is added to the purification solution to remove any V that may be present in the solution. 4+ Completely oxidized to V 5+ An ammonium source is added to the purification solution to induce vanadium precipitation.
[0062] In some embodiments, step S3 includes: adding an oxidant to the purification solution for a third oxidation time, adjusting the pH to 6.5-8.5 with an ammonium source at room temperature-100°C, precipitating for a fourth time, and obtaining ammonium metavanadate precipitate through solid-liquid separation. The pH can typically, but not limitedly, be set to 6.5, 7.0, 7.5, 8.0, or 8.5.
[0063] In some embodiments, the oxidant is NaClO3 or H2O2. The volume of the oxidant added is 3-7% of the volume of the purification solution. Typically, but not limited to, the volume of the oxidant added can be set to 3%, 4%, 5%, 6%, or 7% of the volume of the purification solution.
[0064] In some embodiments, the ammonium source is ammonia, ammonium carbonate, or ammonium bicarbonate. The amount of ammonium source added is sufficient to observe the pH change of the solution to 6.5-8.5. In some cases, the amount of ammonium source added can also be set to 1.5-3 times the vanadium concentration, but this method requires the detection of vanadium concentration. In comparison, directly observing the pH is faster and simpler.
[0065] In some embodiments, the third time is 20-40 minutes. The third time can typically, but not in a limiting way, be set to 20 minutes, 25 minutes, 30 minutes, 35 minutes, or 40 minutes.
[0066] In some embodiments, the fourth time is 1.5-2.5 hours. The fourth time can typically, but not limitedly, be set to 1.5 hours, 2 hours, or 2.5 hours.
[0067] In a specific example, step S3 includes: adding an oxidant (NaClO3 or H2O2) to the purification solution to remove any V that may be present in the solution. 4+ Completely oxidized to V 5+ The pH is adjusted to 6.5-8.5 at room temperature -100℃ using ammonia, ammonium carbonate, or ammonium bicarbonate to generate ammonium metavanadate precipitate. After filtration and washing, high-purity ammonium metavanadate is obtained.
[0068] In step S4, the ammonium metavanadate precipitate is calcined to obtain vanadium pentoxide.
[0069] In some embodiments, step S4 includes: precipitating ammonium metavanadate in an oxygen atmosphere by heating at a rate of 3-10 °C / min, holding at 300 °C for 30 minutes, and calcining at 440-600 °C for 1-4 hours to obtain high-purity vanadium pentoxide. A dynamic calcination process is used to optimize the crystallization properties and particle morphology of V₂O₅. The heating rate can typically, but is not limited to, be set to 3 °C / min, 4 °C / min, 5 °C / min, 6 °C / min, 7 °C / min, 8 °C / min, 9 °C / min, or 10 °C / min. The calcination temperature can typically, but is not limited to, be set to 440 °C, 460 °C, 480 °C, 500 °C, 520 °C, 540 °C, 560 °C, 580 °C, or 600 °C. The calcination time can typically, but is not limited to, be set to 1 hour, 2 hours, 3 hours, or 4 hours.
[0070] In a specific example, step S4 includes: placing the ammonium metavanadate precipitate in a rotary kiln or tube furnace, heating it at 3-10℃ / min in an oxygen atmosphere, holding it at 300℃ for 30 minutes, calcining it at 440-600℃ for 1-4 hours, cooling it out, and crushing the powder to obtain battery-grade V2O5 powder with a purity ≥99.95%.
[0071] In step S5, high-purity vanadium pentoxide is used to prepare the positive electrode material for the battery. For example, the high-purity vanadium pentoxide obtained can be used to prepare the positive electrode material for the LiV3O8 battery.
[0072] In some embodiments, step S5 includes: adding high-purity vanadium pentoxide and a lithium source to an aqueous solution containing a carbon source and ethylene glycol to obtain a raw material mixture; grinding the raw material mixture to a precursor solution with a particle size of 100 nm-3 μm; spray-drying the precursor solution to obtain a precursor powder with a particle size of 10-35 μm; sintering the precursor powder at 350-580 °C and then sieving it to obtain the LiV3O8 battery cathode material. The lithium source is one or more of LiOH·H2O, CH3COOLi·2H2O, LiNO3, and Li2CO3, and the carbon source is C6H... 12 O6·H2O, C 12 H 22 O 11 And one or more of soluble starch. A second aspect of the present invention provides a battery cathode material prepared by the above-described preparation method.
[0073] The present invention will be further described below with reference to specific embodiments, but this does not limit the invention in any way. Unless otherwise specified, all methods used are conventional methods.
[0074] Example 1:
[0075] Preparation method of battery cathode material
[0076] raw material:
[0077] Composition of vanadium-containing leachate (g / L): V 37.4, Fe 2.5, Al 1.2, P 0.4, SiO2 0.8
[0078] Step 1: Preprocessing
[0079] Take 1000mL of leachate, adjust the pH to 2.0 with 10% sulfuric acid, heat to 80℃, add 120g of polyaluminum ferric silicate (1.1 times the theoretical amount), stir for 90 minutes, let stand for 30 minutes, and filter.
[0080] Step 2: Biological-inorganic synergistic impurity removal
[0081] The filtrate was adjusted to pH 3.5 with 20% ammonia, and 0.5g of chitosan (92% degree of deacetylation) and 0.12g of aluminum phosphate gel (1.1 times the theoretical amount) were added. The mixture was reacted at 70℃ for 60 minutes. After filtration, the following results were obtained: Fe 3ppm, Al 2ppm, P 4ppm.
[0082] Step 3: Vanadium Oxidation Precipitation
[0083] Add 5g NaClO3 and oxidize for 30 minutes. Adjust the pH to 7.5 with 15% ammonia water, precipitate at 80℃ for 2 hours, and filter to obtain ammonium metavanadate.
[0084] Step 4: Dynamic Calcination
[0085] With an oxygen flow rate of 1 L / min, the temperature was increased by 5 °C / min, held at 300 °C for 30 minutes, and calcined at 500 °C for 2 hours to obtain a V2O5 product with a purity of 99.96% and a vanadium recovery rate of 98.3%.
[0086] Step 5: Preparation of battery cathode material
[0087] High-purity vanadium pentoxide and LiOH•H2O were added to a solution containing C6H. 12 A raw material mixture was obtained by mixing O6·H2O and ethylene glycol in an aqueous solution. The raw material mixture was then ground to a precursor solution with a particle size of 100nm-3μm. The precursor solution was then spray-dried to obtain precursor powder with a particle size of 10-35μm. The precursor powder was then sintered at 500℃ and sieved to obtain the LiV3O8 battery cathode material.
[0088] Example 2:
[0089] Preparation method of battery cathode material
[0090] raw material:
[0091] Composition of vanadium-containing leachate (g / L): V 35.6, Fe 0.8, Al 0.5, P 0.15, SiO2 0.3
[0092] Step 1: Preprocessing
[0093] Take 2000mL of leachate, adjust the pH to 1.8 with 10% sulfuric acid, heat to 70℃, add 80g of polyaluminum ferric silicate (1.05 times the theoretical amount), stir for 60 minutes, and filter by plate and frame pressing.
[0094] Step 2: Biological-inorganic synergistic impurity removal
[0095] The filtrate was adjusted to pH 3.2 with urea, and 1.0 g of chitosan and 0.18 g of aluminum phosphate gel (1.08 times the theoretical amount) were added. The mixture was reacted at 60°C for 50 minutes. After filtration, the following results were obtained: Fe 2 ppm, Al 1 ppm, P 3 ppm.
[0096] Step 3: Vanadium Oxidation Precipitation
[0097] Add 8 mL of 30% H2O2 and oxidize for 20 minutes. Adjust the pH to 7.0 with ammonium bicarbonate, precipitate at 70℃ for 1.5 hours, and then centrifuge.
[0098] Step 4: Dynamic Calcination
[0099] With an oxygen flow rate of 0.8 L / min, the temperature was increased at 8 °C / min, held at 300 °C for 30 minutes, and calcined at 480 °C for 3 hours to obtain a V2O5 product with a purity of 99.97% and a vanadium recovery rate of 98.8%.
[0100] Step 5: Preparation of battery cathode material
[0101] High-purity vanadium pentoxide and LiOH•H2O were added to a solution containing C6H. 12 A raw material mixture was obtained by mixing O6·H2O and ethylene glycol in an aqueous solution. The raw material mixture was then ground to a precursor solution with a particle size of 100nm-3μm. The precursor solution was then spray-dried to obtain precursor powder with a particle size of 10-35μm. The precursor powder was then sintered at 500℃ and sieved to obtain the LiV3O8 battery cathode material.
[0102] Example 3:
[0103] Preparation method of battery cathode material
[0104] raw material:
[0105] Composition of vanadium-containing leachate (g / L): V 38.4, Fe 1.8, Al 0.9, P 0.3, SiO2 0.6, Ca 0.2
[0106] Step 1: Preprocessing
[0107] Take 1500mL of leachate, adjust the pH to 2.2 with 20% sulfuric acid, heat to 90℃, add 135g of polyaluminum ferric silicate (1.15 times the theoretical amount), stir vigorously for 120 minutes, and filter by pressure.
[0108] Step 2: Biological-inorganic synergistic impurity removal
[0109] The pH of the filtrate was adjusted to 3.8 with NaOH / ammonia (1:1), and 0.75g of chitosan and 0.16g of aluminum phosphate gel (1.12 times the theoretical amount) were added. The mixture was reacted at 80℃ for 80 minutes. After filtration, the following values were measured: Fe 4ppm, Al 3ppm, P 4ppm, and Ca <1ppm.
[0110] Step 3: Vanadium Oxidation Precipitation
[0111] Add 10g NaClO3 and oxidize for 40 minutes. Adjust the pH to 8.0 with ammonium carbonate, precipitate at 85℃ for 2.5 hours, and then filter under vacuum.
[0112] Step 4: Dynamic Calcination
[0113] With an oxygen flow rate of 1.2 L / min, the temperature was increased at a gradient of 3 °C / min, held at 300 °C for 30 minutes, and calcined at 550 °C for 1.5 hours to obtain a V2O5 product with a purity of 99.95% and a vanadium recovery rate of 97.9%.
[0114] Step 5: Preparation of battery cathode material
[0115] High-purity vanadium pentoxide and LiOH•H2O were added to a solution containing C6H. 12 A raw material mixture was obtained by mixing O6·H2O and ethylene glycol in an aqueous solution. The raw material mixture was then ground to a precursor solution with a particle size of 100nm-3μm. The precursor solution was then spray-dried to obtain precursor powder with a particle size of 10-35μm. The precursor powder was then sintered at 500℃ and sieved to obtain the LiV3O8 battery cathode material.
[0116] Table 1 below provides data on the initial vanadium concentration in the vanadium-containing leaching solution used in Examples 1-3, the purity of the final vanadium pentoxide product, and the vanadium recovery rate. It can be seen that: on the one hand, the method of the present invention can prepare vanadium pentoxide with a purity ≥99.95%, meeting battery-grade standards; on the other hand, the vanadium recovery rate of the method of the present invention is ≥97.9%, with a relatively low vanadium loss rate.
[0117] Table 1. Comparison of key data from Examples 1-3
[0118]
[0119] In addition, the solution of the present invention has the following advantages compared with the solution of the prior art: high impurity removal rate, the removal rate of key impurities such as Fe, Al, and P is increased to more than 99.5%, the content of Fe, Al, and P is all <10ppm, and SiO2 <5ppm; short process flow, the production cycle is shortened by more than 30% compared with the traditional method, and energy consumption is reduced by 30%; the use of organic solvents is avoided, wastewater treatment is simple, and it is environmentally friendly.
[0120] Finally, it should be noted that the embodiments described above are only some, not all, of the embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
Claims
1. A method for preparing a battery cathode material, characterized in that, Includes the following steps: S1: Adjust the pH of the vanadium-containing leaching solution to 1.5-2.5, heat the vanadium-containing leaching solution to 60-90℃, then add polyaluminum ferric silicate, stir for a short time, and obtain the pretreated solution through solid-liquid separation; S2: Adjust the pH of the pretreatment solution to 3-4, add chitosan and medical aluminum phosphate gel, react at 60-90℃ for a second time, and obtain the purified solution after solid-liquid separation; S3: Add an oxidant and an ammonium source to the purified liquid to oxidize and precipitate vanadium, and obtain ammonium metavanadate precipitate; S4: Calcining the ammonium metavanadate precipitate to obtain high-purity vanadium pentoxide; S5: Prepare battery cathode material using the high-purity vanadium pentoxide. In step S2, chitosan is first added for adsorption, and then medical aluminum phosphate gel is added.
2. The method for preparing the battery cathode material according to claim 1, characterized in that, Step S3 includes: adding the oxidant to the purified liquid for a third time, adjusting the pH to 6.5-8.5 with the ammonium source at room temperature-100℃, precipitating for a fourth time, and obtaining the ammonium metavanadate precipitate through solid-liquid separation; Step S4 includes: heating the ammonium metavanadate precipitate at 3-10℃ / min in an oxygen atmosphere, holding it at 300℃ for 30 minutes, and calcining it at 440-600℃ for 1-4 hours to obtain high-purity vanadium pentoxide.
3. The method for preparing the battery cathode material according to claim 1, characterized in that, In step S1, the amount of polyaluminum ferric silicate added is 1-1.2 times the theoretical amount, and the first time is 30-120 minutes.
4. The method for preparing the battery positive electrode material according to claim 1, characterized in that, In step S1, the pH of the vanadium-containing leachate is adjusted using a sulfuric acid solution.
5. The method for preparing the battery cathode material according to claim 1, characterized in that, In step S2, the amount of chitosan and medical aluminum phosphate gel added is 1-1.15 times the theoretical amount.
6. The method for preparing the battery cathode material according to claim 1, characterized in that, In step S2, the pH of the pretreatment solution is adjusted using one or more of NaOH, urea, or ammonia.
7. The method for preparing the battery cathode material according to claim 1, characterized in that, In step S2, the second time is 40-90 minutes.
8. The method for preparing the battery cathode material according to claim 2, characterized in that, In step S3, the oxidant is NaClO3 or H2O2, the volume of the oxidant added is 3-7% of the volume of the purified liquid, and the third time is 20-40 minutes.
9. The method for preparing the battery positive electrode material according to claim 2, characterized in that, In step S3, the ammonium source is ammonia, ammonium carbonate, or ammonium bicarbonate, and the fourth time is 1.5-2.5 hours.
10. A battery positive electrode material, characterized in that, It is prepared by any one of the preparation methods described in claims 1-9.
Citation Information
Patent Citations
Preparation of high-purity vanadium pentoxide
CN102849795A
Method for preparing high-purity vanadium pentoxide through sodium salt vanadium precipitation of sodium vanadate solution
CN113800562A
Method for removing metal impurities in ferrous phosphate acid solution and application
CN114572953A
DNA extraction method of jeans inspection material containing trace DNA
CN119061118A